BLOOD URINE POSITIVITY RATE DIPSTICK METHOD ON THE INCIDENCE OF ANEMIA IN URINARY TRACT INFECTION PATIENTS - Siti Zaetun; Lalu Srigede; Nur Sanya Fahmi Mantika (African Journal of Infectious Diseases (AJID), 2025)
Background: The prevalence of anemia in children suffering from urinary tract infections with positive hematuria is very high. UTI is confirmed by a complete urine examination including macroscopic, chemical and microscopic examinations. Chemical examination can be carried out using the dipstick method, while urine microscopy involves looking at the image of the urine sediment. One of the parameters on the dipstick is blood. Examination with a reagent strip (dipstick) function to detect erythrocytes, free hemoglobin and myoglobin. So, the presence of erythrocytes, myoglobin or hemoglobin in the urine will give a positive result on the urine blood dipstick parameters, which means hematuria occurs. Materials and Methods: This is a cross-sectional analytical observational method, namely by comparing the results of blood urine examination using the dipstick method, with the results of the erythrocyte index and hemoglobin levels on the incidence of anemia in UTI patients. Result: The results of the blood urine dipstick examination obtained the highest positive value of 3. The average values for Hb, MCV, MCH, MCHC were respectively 10.9 g/dL, 83.3 fL, 28.5 pg, and 34.24%. Conclusion: The results of the Pearson correlation test obtained a degree of relationship of -0.363 which indicates a weak correlation. Blood urine is negatively related to the incidence of anemia (Hb levels), so that the higher the positive blood urine value, the lower the Hb value.